Inovasi dan Daya Kompetitif Para Wirausahawan UMKM: Dampak dari Globalisasi Teknologi Informasi - Ratiyah Ratiyah; Hartanti Hartanti; Eka Dyah Setyaningsih (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to look at the impact of innovation on competitive advantage along with the role of Information Technology and entrepreneurial orientation as a driver for innovation. The increasingly fierce competition is not only from domestic products but also foreign products that are increasingly free to enter Indonesia. MSME products must be ready to compete on an international scale. If not, many MSMEs in Indonesia will suffer. MSMEs with small capital will also lose out to entrepreneurs with large capital to survive in this globalization influence. The government really must accompany and support the needs of MSMEs to develop and be ready to compete in globalization. The sample consists of MSME Entrepreneurs in the Jakarta area, there are 193 MSME Entrepreneurs who participate. Sampling using purposive sampling from BPS DKI Jakarta data, with criteria for companies that have 10-300 employees and a net worth of 50 million to 2.5 billion (Law Number 20/2008 concerning Micro, Small, and Medium Enterprises). Data were collected through a mail survey (google forms) and analyzed using multiple regression analysis. The results of this study indicate that innovation significantly and positively affects competitive advantage. The influence of Information Technology and entrepreneurial orientation on innovation also has a positive and significant effect. The results of this study also have two implementations: theoretical implementation where the results provide support for the right role of innovation in creating competitive advantage and its role in the Use of Information Technology and entrepreneurial orientation towards innovation. And Managerial implementation that MSME Entrepreneurs must focus on developing organizational values and capacities to encourage the creation of new business solutions. This resource is an entrepreneurial orientation based on information technology. Keywords: Competitive Advantage, Innovation, Information Technology, MSMEs